Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 9175516 species occurrences available in GBIF matching the query: { "Country" : [ "is Brazil" ] } The dataset includes 9175516 records from 1386 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0034265-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences